1965
DOI: 10.1111/j.2042-7158.1965.tb07757.x
|View full text |Cite
|
Sign up to set email alerts
|

Urinary excretion kinetics of methylamphetamine in man

Abstract: The urinary excretion of methylamphetamine and its metabolite, amphetamine, was studied after oral administration of (+)‐ and (–)‐methylamphetamine hydrochloride to three male subjects. Fluctuations in the excretion rate of both amines occurred and were associated with changes in urinary pH. The fluctuations were abolished when the urine was maintained either acid or alkaline, by administration of ammonium chloride and sodium bicarbonate respectively. The total amount of both amines excreted was lower under al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0

Year Published

1988
1988
2010
2010

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 78 publications
(28 citation statements)
references
References 8 publications
0
28
0
Order By: Relevance
“…The transfer of MAMP and AMP into the hair is not known minutely. However, from the studies of the transfer into urine (Dring et al [18], Beckett et al [19] and Caldwell et al [5]) and the reports concerning hair by Ishiyama et al [20], Niwaguchi et al [21] and Suzuki et al [22], we know that excretion rates into urine and hair are quite different, and the optical isomers may not be converted in vivo. We suggest that both abusers tested in the present study abused d-MAMP.…”
Section: Discussionmentioning
confidence: 90%
“…The transfer of MAMP and AMP into the hair is not known minutely. However, from the studies of the transfer into urine (Dring et al [18], Beckett et al [19] and Caldwell et al [5]) and the reports concerning hair by Ishiyama et al [20], Niwaguchi et al [21] and Suzuki et al [22], we know that excretion rates into urine and hair are quite different, and the optical isomers may not be converted in vivo. We suggest that both abusers tested in the present study abused d-MAMP.…”
Section: Discussionmentioning
confidence: 90%
“…The reason for the degree of N-demethylation of S()-MP into the corresponding enantiomer of AP being higher than that of its antipode is unclear. However, it has been reported that the N-demethylation of MP in the human body is an enantiomer-specific metabolic process and the ratios of AP/MP excreted in urine 24 h after an oral dose of 13.7 mg of individual MP enantiomers (n = 3) were 17.8 AE 3.0 and 5.2 AE 1.1% for the S()-and the R(À)-enantiomers, respectively (Beckett and Rowland, 1965). These results are in agreement with our results.…”
Section: Resultsmentioning
confidence: 99%
“…S()-MP hydrochloride was obtained from Dainippon Pharmacy (Osaka, Japan) and R(À)-MP was kindly supplied by Dr S. Ikeda, Kyushu District Narcotics Central Office, Ministry of Health and Welfare, Japan. AP sulfate and p-HMP hydrochloride racemates were synthesized in our laboratory according to known procedures (Nagai, 1893;Buzas and Dufour, 1950). S()-AP and R(À)-AP were a kind gift from Professor T. Nagano, Graduate School of Pharmaceutical Sciences, The University of Tokyo, Japan.…”
Section: Methodsmentioning
confidence: 99%
“…While the major route of elimination for methamphetamine (15,16) and ethylamphetarnine (11), under controlled acidic urinary conditions, is the excretion of the unchanged drug, only 1.5% of orally administered mefenorex was excreted unchanged. Increased metabolism of mefenorex may be associated with the increased lipophilicity of the nitrogen substituent.…”
Section: Resultsmentioning
confidence: 99%
“…Extensive studies on urinary excretion of the unchanged drug and metabolite amphetamine have been made after oral administration of the (+) and/or (-) isomers of N-alkylamphetamines (methyl-, ethyl-, n-propyl-, i-propyl, and n-butyl-) (15,17,18,20). However data on racemic N-alkylamphetamines are insufficient for comparison with those obtained in the present study.…”
Section: Resultsmentioning
confidence: 99%